A polynomial -system with the limit set consisting of four heteroclinic trajectories: A polynomial -system with the limit set consisting of four heteroclinic trajectories - Ruzimuradova, Durdona (MODERN PROBLEMS AND PROSPECTS OF APPLIED MATHEMATICS, 2024)
The limit set of a dynamical system plays an important role in studying its global behavior. It is proved that bounded limit set is a continuum i.e. connected and compact [1, 3, 8]. However, unbounded limit set may have enough complicated structure even for quadratic system [1-10]. We will give an example of the polynomial system in the space , such that the -limit set of some trajectory consists of four heteroclinic trajectories.